Scythian and Anisian beds in the quarry near Hrastenice and important finds of Upper Anisian fossils - Petek, Tomaž (Geologija, 1997)
In an about 150 m thick stratigrafic section in the quarry near Hrastenice I found lower Triassic beds corresponding to Gastropod Oolite Member and to Cencenighe Member of the Dolomites, Lower Anisian dolomite beds and Upper Anisian beds, rich in fossils. Among the ammonoids, six genus occur (Kellnerites, Lardaroceras, Arcestes, Flexoptychites, Gymnites, Monophyllites). On the basis of ammonoids I compared Upper Anisian beds with stratigrafic sections of basinal “Buchenstein Beds” in the Dolomites and Lombardy.